Radiation Detection with G.M. Counter: A Brief Review (Bulletin of Pure and Applied Sciences – Physics, 2021)
The paper aims to present a brief and focused review regarding the mechanism of detection  of radiation with GM Counter and the developments made in this field over the time since the  advent of this Gas detection system. The work done in the field till now is discussed to  showcase the key features of G.M. detector explored till date. This comprehensive review  will stress on the significant developments in the radio-active radiation detection with GM  Counter and a conclusive view-point regarding all the investigations performed in this regard.  A theoretical perspective, along with the overview of recent investigations and related  discussion highlighting the present understanding based on available investigations of  radiation detection with G.M. counter is also presented in a systematic manner. Overall, the  manuscript aims to showcase the fundamental features of G.M. counter detector system as  well as provides overview regarding present understanding of the concept based on the  research work available in the literature.